Improving the Competence of Health Students in Hospital Practice Areas during the Covid-19 Pandemic: Case Study - Agatha Tunjung Dwivania; Lilis Monika Sitohang; Veronika Fernanda Dua Hiko; Mey Lona Verawaty Zendrato (Universitas STRADA Indonesia, 2022)
The COVID-19 pandemic requires changing the learning system in health education institutions. Delayed laboratory practice makes students less skilled in providing nursing actions. This situation was exacerbated when students were required to conduct clinical learning in practical areas during COVID-19. Lack of knowledge and skills, anxiety about the health of themselves and their families, and the absence of an image of caring for patients directly become challenges. The methods case study focuses on articles conducted during clinical learning at the Regional General Hospital (RSUD) X in Jakarta. There were challenges and obstacles when students did clinical learning. Challenges a present internally and externally. Cooperation is needed from both the institution and the field of practice to assist and guide students. However, students must take the initiative and be critical to creating a gradual increase in skills followed by new things learned while in practice.